Gender Gap in Housework: Couples' Data Analysis in Kyrgyzstan. - Kolpashnikova, Kamila; Kan, Man-Yee (Journal of Comparative Family Studies, 2020)
We analyze couples' time-use diaries from the 2012–2013 Life in Kyrgyzstan data. Using the pooled Blinder-Oaxaca decomposition method, we test the relative resources, time availability, absolute resources, and gender-centered frameworks in their ability to explain gender differences in housework participation among Kyrgyzstani women and men. The results show that among the three resource-based approaches, the time availability models are the most potent in accounting for the gender gap in housework, followed by the relative resources framework. Both frameworks emphasize household bargaining processes and power differentials between spouses. The findings suggest that among Kyrgyzstani couples, partners' time availability and, with it, bargaining power play an important role in the division of housework tasks. In contrast, absolute resources can account only for a small portion of the gender differences in housework participation.